A new flash boiling model for single droplet. (April 2017) - Xi, Xi; Liu, Hong; Jia, Ming; Xie, Maozhao; Yin, Hongchao
Highlights: A series of new flash boiling sub-models inside a droplet has been proposed. The bubble growth model couples with the classical homogeneous nucleation model. Evolution behavior of bubble growth can be divided into three distinct stages. The effect of superheat temperature plays a significant effect on bubble nucleation and growth. Both of ambient pressure and initial temperature operate on explosion boiling time. Abstract: A series of new flash boiling sub-models inside a droplet were proposed in this study. Compared to the previous flash boiling model, the proposed model includes the classical homogeneous nucleation sub-model, the Rayleigh bubble growth sub-model, and a new bubble explosion sub-model. Both the energy and momentum balances inside a droplet are considered. By coupling with the variation of the fuel thermo-physical properties with temperature, the criterion of the bubble nucleation, growth, and explosion criteria are well predicted. The model is validated by the experimental data of superheated water. The computational results indicate that the flash boiling process can be divided into three stages, i.e., the initial stage controlled by the surface tension of the fuel, the rapid growing stage controlled by the heat diffusion in the droplet, and the final explosion stage. Based on the present model, the boiling explosion time is quantitatively provided at wide ranges of fuel temperature and ambient pressure which have the vital significance in predicting the secondary breakup of the droplet.